Seasonal variations in phytoplankton diversity in the Bui dam area of the Black Volta in Ghana during the pre- and post-impoundment periods - Alhassan, Elliot Haruna (Revista de Biología Tropical, 2015)
Phytoplankton constitutes the primary producers of aquatic ecosystems and represents the food chain base that supports the commercial fisheries of most water bodies. Nowadays, there is lack of information on phytoplankton assemblages of most reservoirs in Africa. To contribute with this knowledge, this study was carried out to determine the density and diversity of seasonal variations of phytoplankton species in the Bui dam area of the Black Volta, during the pre- (2011) and post-impoundment (2012) periods. For this, a three-level stratified random sampling approach was adopted for 22 months. Phytoplankton samples were obtained by towing a 0.5m diameter phytoplankton net (35μm mesh size and 0.25m2 mouth surface area) from a non-motorized canoe through a distance of about 100m against the current from downstream to upstream of the river. In 2011, 35 species of phytoplankton belonging to four classes, Bacillariophyceae (7.6%), Chlorophyceae (43%), Cyanophyceae (48.6%) and Euglenophyceae (0.8%) were identified. In the 2012 sampling, 18 species belonging to three classes, Bacillariophyceae (2.2%), Chlorophyceae (26.1%) and Cyanophyceae (71.7%) were observed. A total of 17 species of phytoplankton, including Gyrosigma sp., Surirella sp., Carteria sp., Chlosterium sp., Chlorogonium sp., Coelastrum sp., Cosmarium sp., Volvox sp., Chroococcus sp., Coelosphaerium sp., Rivularia sp. and Spirulina sp., were absent during the late post-impoundment period. Mean monthly total phytoplankton abundance decreased from June (7 384 cells/m3) to August (106cells/m3) in 2011. In 2012 however, mean total phytoplankton decreased from February (1 237cells/m3) to August (4cells/m3). The results also showed that variations occurred between seasons among some phytoplankton groups. The dry and pre-wet seasons had significantly (p<0.05) higher mean phytoplankton abundance than the wet season during the 22 months of sampling period. The biotic indices of Shannon-Wiener (H1) were homogenously distributed in the four hydrological seasons of the two years. The phytoplankton groups, Bacillariophyceae, Chlorophyceae, Euglenophyceae and total phytoplankton differed significantly (p<0.05) between the pre- and post-impoundment periods. The total phytoplankton was also significantly (p<0.05) higher in the upstream station than the downstream station indicating the impact of the impoundment on the downstream ecology. Hence, river management strategies should be implemented by hydro-biologist to lessen the impact of the dam on the downstream ecology.